Respuesta :
subtract 9x from its side and move it over, -9x+y=7/3 should be your answer, hope i helped
Answer:
[tex]3x-1y=-\frac{7}{3}[/tex]
Step-by-step explanation:
We've been given the equation [tex]y=\frac{9x+7}{3}[/tex]
In order to bring it in the standard form we must write it as Ax + By = C
First, we need to split and divide both the terms of the numerator by 3 on the right side
[tex]y=\frac{9x}{3}+\frac{7}{3}[/tex]
Simplifying [tex]\frac{9}{3}[/tex], we get 3
[tex]y=3x+\frac{7}{3}[/tex]
Subtract [tex]\frac{7}{3}[/tex] from both side
[tex]y-\frac{7}{3}=3x+\frac{7}{3}-\frac{7}{3}[/tex]
Cancel out [tex]+\frac{7}{3}[/tex] and [tex]-\frac{7}{3}[/tex] from the right side
[tex]y-\frac{7}{3}=3x[/tex]
Subtract y from both sides
[tex]y-\frac{7}{3}-y=3x-y[/tex]
Cancel out y and -y on the left side
[tex]-\frac{7}{3}=3x-y[/tex]
y is written as 1y
[tex]-\frac{7}{3}=3x-1y[/tex]
Flip the sides
[tex]3x-1y=-\frac{7}{3}[/tex]